Alarming development of dual snus and cigarette usage among young Finnish males - Maria Danielsson; Anelma Lammi; Simo Siitonen; Jukka Ollgren; Liisa Pylkkänen; Tuula Vasankari (BMC, 2019)
Abstract Background The consumption of tobacco products has evolved to include more complex combinations of different products. We investigated the tobacco habits of a representative population of young Finnish male conscripts in order to evaluate the prevalence of dual use of cigarettes and snus as well as the transition from one tobacco product to another. In addition, we evaluated the correlation between the level of education and the use of cigarettes and snus. Methods A questionnaire-based survey was carried out in three out of 17 garrisons among conscripts during their first week of service in 2014. A total of 1971 male conscripts were selected by simple random sampling of the 9013 males in the selected garrisons. Of them 1916 participated and filled in the questionnaire. The response rate was 97.2%. The questionnaire consisted of 25 questions including age, gender, basic education, use of tobacco products as well as questions assessing nicotine dependency. Results The amount of dual users of cigarettes and snus was 21%. There was a higher probability of dual use of cigarettes and snus among smokers compared to snus users (p < 0.001). One third (35%) of former smokers reported daily snus use and over 40% of the former snus users smoked daily. One third (34%) of the participants reported snus usage and 14% of the study subjects used snus daily. 40% of the study population were smokers and over 25% smoked daily. Of the participants with basic educational background 57% smoked daily (p < 0.001), however, no association between snus and level of education was found (p = 0.69). Conclusions This study provides better understanding of the complex tobacco habits of young adult males. The simultaneous usage of multiple tobacco products as well as the high tendency to transition from one tobacco product to another should be taken into consideration when planning cessation interventions in health care settings and tobacco control policies at societal levels.